Analisis Faktor Produksi Dan Efisiensi Alokatif Usahatani Bayam (Amarathus Sp) Di Kota Bengkulu - Fithri Mufriantie; Anton Feriady (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2014)
Abstract. The purpose of this study is (1) determine the factors that affect farm production spinach (2) determine the level of allocative efficiency of the use of production factors that affect farm production spinach (3) determine the level of farmers'income spinach. The study was conducted in the city of Bengkulu were selected intentionally (purposive sampling) include tebeng village gardens, the Village Land of Broken Bridge Village and Small with the consideration that the area is a center for vegetable planting. The samples used in this study were 36 farmers were taken with the Proportional stratifies random sampling method. The results found that overall (simultaneously) the observed variables significantly affect production, while partial variabel land area (X1), urea (X3), manure (X4) and labor (X5) does not significantly affect the production and variabel seeds (X2) significantly affected the production of spinach. Allocative efficiency analysis shows that the factors of production of seed and manure inefficient use may need to be added while the land area for production factors, urea fertilizer and labour should be reduced because it is not efficient in its use.